Molecular detection of Theileria spp. in native sheep and estimation of hemato-biochemical parameters from Sulaimani province/Iraq - Abdullah, Shadan Hassan; Dyary, Hiewa Othman; Saeed, Nahla Mohammed (Frontiers in Veterinary Science, 2022)
Theileriosis, the hemoprotozoan infection, is an endemic condition in tropical and subtropical areas. In this study, conventional PCR analysis was applied to detect the natural infection of native sheep with theileriosis and estimate its effect on hemato-biochemical parameters. The study was carried out in nine districts of Sulaimani province, northern Iraq. From May to October 2021, a total of 360 blood samples were collected randomly from the jugular vein of sheep belonging to 23 herds with a history of tick infestation. Following PCR screening for theileriosis, Hemato-biochemical parameters were evaluated by an automatic analyzer using commercial kits. The PCR results repented that 71.6% of examined sheep were infected with Theileria parasites. The hemogram data revealed a significant decrease in erythrocyte count, hemoglobin concentration, and hematocrit values. Erythrocyte indices also showed significant increases in MCV, MCH, and MCHC levels, but no significant differences were detected between the counting of leukocytes, lymphocytes, and granulocytes. Biochemical analysis revealed a significant decrease in total proteins, albumin, and creatinine levels with a significant increase in Urea and AST levels in infected sheep with theileriosis. Alteration in Hemato-biochemical parameters from infected animals can outline the impact of theileriosis on body metabolism and blood factors in naturally infected sheep.